Influence of I’rab to Meaning: Analysis Study based on Qutrub Perspective - Hadi, Al Amin; Firdaus, Rijal; Ardinal, Eva; Fikri, Ahmad (Al-Ma‘rifah, 2023)
The researcher in this paper explores the topic of Arabic grammar and its significance in the Arabic language. To showcase the nature of Arabic grammar and its position in the language, the researcher begins by collecting definitions of Arabic grammar from linguists. The researcher then delves into Qatrub's theory on the impact of Arabic grammar on the meanings of the Arabic language and analyzes his deviation from the majority of grammarians' views. This research is conducted through library research, gathering the necessary data and information related to the topic. After analyzing Qatrub's theory, the author draws conclusions, Regarding the Arabic grammar's impact on the meanings of the language, the researcher concludes that it has an important position in Arabic. However, linguists are divided into two groups: one group believes that Arabic grammar has an impact on the meanings of the Arabic language, while the second group believes that Arabic grammar has no essential semantic value. Qatrub's deviation from the majority of scholars or their consensus is attributed to the isolationist thinking, which was characterized by scientific liberation and the prioritization of reason, even if it contradicts religious texts or the consensus of the people.